The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s11910-016-0674-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Effects of Cerebral Amyloid Angiopathy

Abstract: Cerebral amyloid angiopathy is a condition of the cerebral arterioles and to a lesser extent capillaries and veins, wherein beta-amyloid is deposited. In arterioles, this preferentially targets vascular smooth muscle cells and in the later stages undermines the stability of the vessel. This condition is frequently comorbid with Alzheimer's disease and its role in cognitive impairment and dementia is a topic of considerable recent research. This article reviews recent literature which confirms that CAA independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…16,17 The presence of WMD on imaging is a useful biomarker for compromised cognitive performance, particularly on measures of memory and processing speed. 17,18 Common pathologic correlates of WMD include those commonly implicated in neurodegeneration, such as elevated markers of axonal damage, the presence of activated microglia, and disorganization of aquaporin-4 localization on vessel-associated astrocytes. [19][20][21][22] Mechanisms by which WMD may exert a negative effect on outcomes following an acute stroke are multifold.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 The presence of WMD on imaging is a useful biomarker for compromised cognitive performance, particularly on measures of memory and processing speed. 17,18 Common pathologic correlates of WMD include those commonly implicated in neurodegeneration, such as elevated markers of axonal damage, the presence of activated microglia, and disorganization of aquaporin-4 localization on vessel-associated astrocytes. [19][20][21][22] Mechanisms by which WMD may exert a negative effect on outcomes following an acute stroke are multifold.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the clinical observation of cognitive impairment in CAA, the frequency, severity, and specific cognitive profile of CAA patients are not well understood (Schrag and Kirshner, 2016). To address this question, a pilot study reported neuropsychological and neuroimaging data from an ongoing prospective cohort (Functional Assessment of Vascular Reactivity in CAA) (Case et al, 2016).…”
Section: Dementia and Cognitive Impairment In Cerebral Amyloid Angiopmentioning
confidence: 99%
“…The etiology of CMH includes CAA, hypertension, Alz heimer's disease, vascular dementia and genetic microvascular disease, but the pattern of neuroimaging findings on SWI in IE is characteristic [19,20] . They are common and distributed broadly, but have a preference for the posterior circulation, particularly the cerebellum.…”
Section: Discussionmentioning
confidence: 99%